Analisis Pengaruh Stres Kerja, Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Kantor Satuan Polisi Pamong Praja (Satpolpp) Kabupaten Alor - Rupus Letmau (Jurnal Ilmiah Wahana Pendidikan, 2023)
The porpuse thisstudy was to determine the effect of work stress, work enviromen and organizational cimmitmen on employee performance at the Civil Service Police Unit Office (SATPOLPP) in Alor Regency. This type of research is a quantitative description. Samples were taken using saturated sampling technique. The sampling in this study were 82 employees. Data collection tools used are observation, interviews, questionnaries and literature studies. The data analysis model used to answer the hypothesis is multiple analysis, t test F test using SPSS version 22 for windows. This research instrument test is used to measure the level of validity, reliability and classic assumptions from the answer to the research questionnaire. By using the tool to calculate SPSS versi 22 For Windows. Baset on the results of the validity test for each variable with a pearson correlation value ≥ 0.3, the results of the validity test for each variable are declared valid. The reliability test results for each variable with a Crobate Alpha value of 20,6, the reliability test results for each variable are declared reliable. Shapiro-Wilk Normality test results with sig. > 0.05 then the test results are declared normal. The results of the heteroscedasticity test showed thad the value of each independent variable was ˃ 0.05, so there was no heteroscedasticity in this study. The results of the multicollinearity test show that the VIF ˃ tolerance value means that multicollinearity does not occur in this study. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity vlue is ˃ 0.05, so there is a relationship between the dependent variable and the independent variable. The analytical method used is multiple linear regression analysis technique. The results with the test to answer the first, second, and third hypotheses, while multiple linear regression analysis simultaneously used the F test to determine the fourth hypothesis, namely to determine the effect of work Stress, work Environment and Organizational Commitment on Employee Performance at the Civil Service Police Unit Office (SATPOLPP) Alor Regency. Based on the results of multiple linear regression analysis calculatios partially and simultaneously, the significance value of the work stress variable is 0.000, the work environment variable is 0.000,the organizational commitment variable is 0.004 end thesimultaneous effect of the value of the significance test F 0.000, the results of the t test and the F test is smaller than alpha (0.05), then the hypothesis testing proposed in this study is as follows: There is an Effect of Work Stress, Work Envronment and Organizational Commitment on Employee Performance at the Civil Service Police Unit Office (SATPOLPP) Alor Regency.